The Role of Effective Communication Training to Improve Skills and Productivity by the Sikka Regency Manpower and Transmigration Service - Silvesta, Yosefina Pausta; Mustafa, Intan; Sedu, Viktor Ariestyan (Jurnal Indonesia Sosial Sains, 2025)
Effective communication is crucial in enhancing skills and productivity in various sectors, including community and organizational development. Conflicts often arise in daily interactions, and effective communication plays a pivotal role in identifying and resolving these issues constructively. This research aims to describe the activities carried out during training organized by the Sikka Regency Manpower and Transmigration Service at the Karya Ilahi Foundation and Avco Dai Adaesa Bola Processing to find out the role of effective communication in improving skills and productivity at the Karya Ilahi Foundation. Researchers used descriptive qualitative research methods. Data collection techniques use observation and documentation. The results show that with effective communication, conflicts can be identified and resolved in a constructive way. Interesting during the training at the divine work foundation: This training provides a number of materials about dealing with children with special needs, so that teachers and employees are better prepared to deal with various situations in the school environment. Providing this training helps the community to better utilize local resources such as coconut which can be processed with various types, one of which is VCO.